2021
DOI: 10.1088/1757-899x/1144/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Fruit Wastes (Jackfruit and Mango Seeds and Banana Trunk) as Natural Coagulants in Treating Municipal Wastewater

Abstract: The adequacy of chemical coagulant such as alum is all around perceived. However, there are numerous drawbacks including impeding impacts on human well-being and generation of high sludge volumes. Therefore, this study was conducted to investigate potential of fruit wastes - jackfruit (artocarpus heterophyllus) seeds, banana trunk peduncles (musa) and mango (mangifera indica) seeds in becoming natural coagulant to treat wastewater. A series of jar test was performed to determine the effect of individual coagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The coagulating active components believed to be proteins was found to constitute up to 58 % of the mango seed [ 13 ]. Using sodium hydroxide (NaOH) and NaCl extraction solvents, the coagulating active component of the mango seed kernel was found to be 25.1 % and 49.75 %, respectively [ 14 ]. Results from this study showed that the protein content of a plant part (such as the mango seed in this case) depends on the extraction solvent used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coagulating active components believed to be proteins was found to constitute up to 58 % of the mango seed [ 13 ]. Using sodium hydroxide (NaOH) and NaCl extraction solvents, the coagulating active component of the mango seed kernel was found to be 25.1 % and 49.75 %, respectively [ 14 ]. Results from this study showed that the protein content of a plant part (such as the mango seed in this case) depends on the extraction solvent used.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, turbidity removal efficacy of 98.6 % was found under an optimum condition of 0.5 mL/L of mango seeds at pH of 13 to treat synthetic turbid water with turbidity values in the range 17.5–90 NTU [ 13 ]. The optimum turbidity removal of Mango seed was also achieved using dosage of 100 mg/L under pH of 6 or 9 [ 14 ]. The potential of M .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, agro-wastes with high moisture content tend to possess a shorter lifespan as they will decompose or even rot faster than oven-dried sources [20]. Not limited to that, raw agro-wastes with high moisture content will be difficult to grind as water act as a plasticizer that bridge the particles, hence increasing the cohesiveness of the powder [21,22]. Many studies have been carried out on different types of natural coagulants.…”
Section: Physicochemical Characteristics Of Bagassementioning
confidence: 99%
“…Despite not having a rough and porous surface area, bagasse has a large surface area that can enhance the interparticle bridging mechanism. In addition, according to Shahimi et al [22], bagasse can still become a good natural coagulant by removing significantly high turbidity content.…”
Section: Surface Morphology Of Saccharum Officinarummentioning
confidence: 99%